Hand Machinery Injuries Presentation and Management (Omdurman Teaching Hospital) (Global Journal of Medical Research, 2014)
Aim to evaluate the amplitude of MHI received by OTH. This prospective descriptive cross sectional hospital base study carried out in a single plastic surgery unit at OTH in the period from sep 2012- sep2013. A total of 106 MH injured patients were enrolled in this study; Evaluation is purely clinical and radiological. Initial management included general assessment of the patient status, wash of the wound with antiseptic, careful limited initial debridement, elevation of the hand, antibiotic and anti tetanus prophylaxis. Beside exploration of the wound with proper surgical management according to the injury ranging from minimal stitching, V.Y flap, skin graft, vessel, nerve, tendon repair to bone fixation .with severely crushed hand a limited stitching and waiting for 48 h before a second look. The study revealed that the right hand dominance was prevalent in 97.2% and was the most affected (64.1% ). The mean age of the study group 25 years with male to female ratio of 4:1. Among named machines, Grinder injury is the commonest represent about (36.8%); followed by plastic machine 8.7%. The most involve part of the hand is the middle finger 14.2% , index 10.4% and thumb 8.5% .Highest percentage of fractures found in the middle finger 15.1% . Skin loss was seen mainly in index finger 4.7%. Concerning the management at tertiary hospital, minimal stitching constitutes 55.7% followed by V.Y flap 7.5%. Amputation in MHI is of great significance of P- value < 0.03, at initial discharge from ER; thumb represent (2.8%), and index (4.7)% Conclusion : Severe hand injury in form of finger amputation, skin loss, nerve and arterial injuries are more common in age below 25 years. Grinder and plastic machines are the commonest cause of MHI among named machines
Keywords: grinder; finger; amputation; crush; palm